The Potential Treatment of Guava Leaf (Psidium guajava Linn.) For Diarrhea in Children - Extin Faulinza (Eureka Herba Indonesia, 2021)
Diarrhea is one of the common health problems which is causes death in children especially in a developed country. Not everybody can access the diarrhea treatment suggested by WHO. Some people decided to utilize alternative treatment, such as the medicinal plant in their environment. It is cheaper and easier to get. One of herb plant that uses is guava leaf (Psiidium guajava Linn.). It contains some active ingredients such as quercetin, tannins, flavonoids, and phenols which have the potential to antidiarrheal activity. To date no death or unusual behavior reported. Guava leaf (Psiidium guajava Linn.) extract can be provided as potential antidiarrheal in children.